A Semantic Based Certification and Access Control Approach Using Security Patterns on Seagent - Tekbacak, Fatih; Tuğlular, Tuğkan; Tuğlular, Tuğkan; Dikenelli, Oğuz (Knowledge Systems Institute, 2008)
In this paper, we propose a security infrastructure for communication between agents adaptable to FIPA security specifications by employing security patterns and semantic based policy descriptions. Security patterns are used as a generalized approach for generating security based services. This paper analyzes the authentication and semantic based access control among agents by using the security patterns.
20th International Conference on Software Engineering and Knowledge Engineering, SEKE 2008; San Francisco Bay, CA; United States; 1 July 2008 through 3 July 2008
Keywords: SEAGENT; Security patterns; Control approach; Access control